Burden and vulnerability of hypertension in a rural population of Patna, Bihar, India (South East Asia Journal of Public Health, 2013)
Population based studies on hypertension from rural Bihar have not been reported earlier. We conducted a study to find the prevalence and the risk factors of hypertension in a rural adult population. In this cross-sectional community based study, 1083 men and women, aged 30 years and above, residing at 10 randomly selected villages of Phulwarisarif Block of Patna District of Bihar were recruited. Using house to house interviews with a semi-structured pretested schedule, the sociodemographic risk factors were recorded. Hypertension and pre-hypertension were classified using JNC-VII criteria. Overall prevalence of hypertension was 23.73%; among them mean systolic and diastolic blood pressures were 144.8±17.14 and 89.04±9.25 mm of Hg respectively. Among those who were hypertensive, the age cluster was higher (50.6±12.7 years) than those who were normotensive (43.8±12.4 years) with a significant male preponderance. Hypertension was significantly associated with a higher body mass index, waist-to-hip ratio, along with the sedentary lifestyle. However, there was not an association with consumption of alcohol and smoking. The study highlighted the need for initiation of high risk hypertension screening in rural Bihar as the awareness on and its risk factors was very low. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13221 South East Asia Journal of Public Health 2011:1:53-58